Exploring the applicability of SERVPERF model in Indian two-wheeler industry: a CFA approach. (10th March 2020) - Nasir, Mohd; Adil, Mohd
For over the years, after-sales service (ASS) has assumed its importance in an automotive industry. Although, an adequate number of scales and model sexist to measure ASS quality, yet extant literature provides evidences in support of two established and well known models/scales viz. SERVQUAL and SERVPERF. But, researchers have raised concerns related to its applicability in a multi-cultural business environment like India. Thus, this study attempts to examine the applicability of original SERVPERF model in Indian two-wheeler industry. Combinations of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) techniques have been used to understand the item structure, dimensionality and psychometric properties of the scale. Results in this study fail to support the item structure of original SERVPERF model as proposed by Cronin and Taylor (1992). We strongly suppose that this variation is context specific and less generic as originally contended. These results suggest that relying service quality assessment on the original SERVPERF items can be misleading in Indian context. As such, context-specific 18-items are therefore needed to assist Indian automobile companies in their service quality improvement programs. If this fit is achieved, the general welfare of consumers' vis-à-vis service quality may be enhanced.